SÍNTESE, CARACTERIZAÇÃO E AVALIAÇÃO BIOLÓGICA DE UM NOVO COMPLEXO QUERCETINA - PRATA(I) - Teixeira, E. I.; Gonçalves, A.; Pinheiro, A. C. N.; dda Cruz, M. M.; Faganello, N. L; dos Anjos, A. (ANAIS DO ENIC, 2017)
-